Coenological and grassland management studie in different planted and renewed grasslands - Uj, Boglárka; Juhász, Lajos; Szemán, László; ifj. Viszló, Levente; Penszka, András; Szentes, Szilárd; Tóth, Andrea; Penszka, Károly (Acta Agraria Debreceniensis, 2013)
We studied the vegetation of a 260 ha Hungarian Grey Cattle pasture near Páskom, which can be found in Zámoly basin. We carried out our surveyes in May 2012. The pasture can be divided into five parts. One part, approximately the half of the area (150.83 ha), is an old-field grassland, which was overseeded 20 years ago. The other half of the pasture was restored (109.17 ha) in 4 different ways in 2009 and then was mowed until 2011. Seven relevés were made in each part of the pasture (the occurence of species and their cover value were recorded). The aim of our study was to compare the effects of the different restoration methods and mowing on the botanical composition of the pasture.The results showed, that the grassland restored with hay transfer method was the most similar to the natural conditions. The greatest number of species was recorded in that part and the species of natural grasslands become dominant. The directly sowed and the spontaneous grassland parts separated chiefly from the semi-natural 20 years old grassland.